Antimicrobial susceptibility patterns of Salmonella typhi and Candida Albicans isolates in Dar es Salaam, Tanzania (Tanzania Medical Journal, 2007)
The aim of this study was to determine antimicrobial susceptibility testing patterns of Candida Albicans and Salmonella typhi isolates. Fifteen isolates of each microorganism were collected from three hospitals located in Dar es Salaam region within a 3-month period in the year 2005. Candida Albicans and Salmonella typhi isolates were purified by sub-culturing on appropriate culture media in order to obtain pure cultures of the assayed microorganisms. Candida Albicans isolates were identified by Gram staining technique and germ tube test, while Salmonella typhi isolates were also identified by Gram staining technique followed by sub-culturing in various selective and differential culture media, then confirmed by immunological (agglutination) test. In-vitro antimicrobial susceptibility patterns of the assayed microbial isolates were determined by the disk diffusion technique of Stokes. The disk strength and tentative sizes of zones of inhibition (ZI) were interpreted in accordance with American National Committee for Clinical Laboratory Standard (NCCLS). Antifungal susceptibility patterns for Candida Albicans isolates showed that azoles are more efficacious than other assayed antifungal agents. Results of antibacterial susceptibility revealed that all the assayed S. typhi isolates were resistant to chloramphenicol and co-trimoxazole, but were sensitive to ciprofloxacin, gentamicin, ampicillin, doxcycline and ceftriaxone. Therefore, this study finding calls for a need to review the current prescription and dispensing practices of antimicrobial agents in both hospitals and pharmacies respectively. Furthermore, it is recommended that a nationwide study on antimicrobial susceptibility pattern should be conducted in order to come up with national policy on rational use of antibiotics. Keywords: Susceptibility patterns testing, antimicrobial agents. Tanzania Medical Journal Vol. 21 (1) 2006: pp. 13-16